Immunogenomic analysis of the tumour microenvironment - Chi, Y (2022)
Immune signatures are important tools to investigate the prognostic significance and therapeutic possibilities of different immune populations in the context of the tumour microenvironment (TME). Accompanied by the wealth of cancer transcriptomic data, many immune signatures have been developed using different samples, technologies, and methods. But there has been limited effort to comprehensively assess these tools in cancer, especially in the context of macrophage signatures.